Characterization of a Cd2+-resistant plant growth promoting rhizobacterium (Enterobacter sp.) and its effects on rice seedling growth promotion under Cd2+-stress in vitro - Pramanik, Krishnendu; Mitra, Soumik; Sarkar, Anumita; Soren, Tithi; Maiti, Tushar Kanti (Agriculture and Natural Resources, 2018)
Rhizosphere contamination due to heavy metals in agriculture leads to decreased production of edible crops. High water solubility and permeability of these life-threatening metals lead to increased translocation to the upper part of plants and the accumulation of these metals in food crops including cereal seeds. Apart from conventional methods, plant growth promoting rhizobacteria (PGPR)-influenced bioremediation is now an emerging, eco-friendly and inexpensive tool. The K2 isolate is one such multiheavy-metal-resistant PGPR isolated from the metal-contaminated rice rhizosphere. The isolate was identified as Enterobacter sp. using phenotypic characterization and MALDI-TOF MS-based ribosomal protein data. The strain was able to resist a group of heavy metals/metalloids (Cd2+, Pb2+, As3+, Ni2+, Hg2+) up to certain levels. The strain possessed a collection of PGP traits such as phosphate solubilization, Indole-3-acetic acid production, 1-aminocyclopropane-1-carboxylic acid deaminase activity and nitrogen fixation. In vitro growth enhancement of a rice cultivar by the strain was investigated using Cd2+ stress, as observed in various growth parameters (seed germination, root-shoot length, root-shoot biomass, seedling vigor index, chlorophyll content). Hence, the K2 strain can be exploited regarding multi-heavymetal/metalloid contamination for effective growth promotion under stress conditions for sustainable agriculture.